2008
DOI: 10.1016/j.jneumeth.2008.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptors in human lymphocytes: Radioligand binding and quantitative RT-PCR assays

Abstract: Analysis of dopamine receptors (DR) in lymphocytes of the human peripheral blood mononuclear cell (PBMC) fraction is an attractive tool for evaluation of functional properties of dopaminergic function underlying variation in complex psychological/psychopathological traits. Receptor binding assays (RBA) with selective radioligands, which are widely used in CNS studies, have not produced consistent results when applied to isolated PBMC. We tested the assay conditions that could be essential for detection of DR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 64 publications
(107 reference statements)
4
46
0
3
Order By: Relevance
“…This suggests that PMC molecular markers may be useful in investigation of the mechanism of action of treatment over time. The PMC gene expression changes occurred in parallel to clinical improvements in schizophrenic patients consistent with the study of Kirilova et al (16). Also, the profile of dopamine receptor genes may be specific with type oftreatments that report similar results in other studies (17)(18).…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that PMC molecular markers may be useful in investigation of the mechanism of action of treatment over time. The PMC gene expression changes occurred in parallel to clinical improvements in schizophrenic patients consistent with the study of Kirilova et al (16). Also, the profile of dopamine receptor genes may be specific with type oftreatments that report similar results in other studies (17)(18).…”
Section: Discussionsupporting
confidence: 87%
“…DRs are differentially expressed on dopaminergic neurons throughout the brain and can also be found on a number of other cell types, including immune cells and glia. 25,37,38,57 DA plays an important role in many neurological disorders such as Parkinson's disease but has not been well examined in the context of HIV-induced neuropathology. In simian immunodeficiency virus-infected macaques, a model for neuroAIDS, administration of the DA-enhancing substances L-DOPA and selegiline increased CNS viral load and accelerated the development of neuropathology.…”
Section: Discussionmentioning
confidence: 99%
“…25 Classically, DRs have been studied on neurons, but DR expression has also been reported in several types of peripheral blood leukocytes, including T lymphocytes and monocytes. [37][38][39] Dopamine receptors have been shown to modulate the immune function of T lymphocytes. 25,40,41 A recent study showed D1R on human macrophages, 24 but the expression of other DRs and the functions of DRs in this cell type have not been well characterized.…”
Section: Human Immunodeficiency Virus (Hiv) Enters the Central Nervoumentioning
confidence: 99%
“…Indeed, both primary and secondary lymphoid organs contain high levels of dopaminergic nerve terminals (3)(4)(5). Moreover, many circulating immune cells, including monocytes, neutrophils, eosinophils, B cells, T cells, NK cells, and dendritic cells (DCs), constitutively expresses DA receptors (DARs) on their surface (6)(7)(8)(9)(10). The engagement of DARs on these immune cell compartments is associated with the regulation of several important cell functions, such as cellular proliferation and division, cytokine production, cell polarization, and migration (11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%